2004
DOI: 10.1093/pcp/pch023
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Acetaldehyde in Seed Deterioration of Some Recalcitrant Woody Species through the Acceleration of Aerobic Respiration

Abstract: The rate of acetaldehyde (Ald) evolution in the deterioration of recalcitrant woody seeds was investigated. Four plant species, Ligustrum japonicum, Quercus serrata, Quercus myrsinaefolia and Camellia japonica, were used for the experiments. Similar to orthodox seeds, all of the recalcitrant seeds used contained Ald in addition to methanol and ethanol, although the amount of Ald in Camellia, a typical oil seed, was very small. These volatiles were accumulated in a container in which Ligustrum and Q. serrata se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The mitochondrial membrane is known to be among the primary sites of deterioration, for instance, during seed ageing, because mitochondrial activity has been clearly demonstrated to be the primary source of energy (adenosine triphosphate) for cells (Delouche and Baskin, 1973;Nelson and Cox, 2012). A decrease in the mitochondrial efficiency is correlated with an increase in the production of volatile compounds, especially ethanol (Akimoto et al, 2004;Colville et al, 2012;Mira et al, 2016;Woodstock and Taylorson, 1981). In the past, the method has been based on benchtop multiparameter instruments, using gas chromatography or enzyme sensor technology, both of which are slow and costly for routine analyses of multiple samples (Bicanic et al, 2003;Kataki and Taylor, 2001;Mira et al, 2010;Mira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial membrane is known to be among the primary sites of deterioration, for instance, during seed ageing, because mitochondrial activity has been clearly demonstrated to be the primary source of energy (adenosine triphosphate) for cells (Delouche and Baskin, 1973;Nelson and Cox, 2012). A decrease in the mitochondrial efficiency is correlated with an increase in the production of volatile compounds, especially ethanol (Akimoto et al, 2004;Colville et al, 2012;Mira et al, 2016;Woodstock and Taylorson, 1981). In the past, the method has been based on benchtop multiparameter instruments, using gas chromatography or enzyme sensor technology, both of which are slow and costly for routine analyses of multiple samples (Bicanic et al, 2003;Kataki and Taylor, 2001;Mira et al, 2010;Mira et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Kodde et al (2012) reported a fast and reliable method to evaluate seed viability or deterioration using a modified ethanol sensor, or breath analyser, a so-called fast ethanol assay. In a fast ethanol assay, ethanol production by partially imbibed seed is a potential indicator of seed vigour because production from deteriorated seed is relatively high compared to that from high-vigour seed (Akimoto et al, 2004;Buckley and Huang, 2011;Kataki and Taylor, 2001;Kodde et al, 2012). The generation of ethanol can indicate loss of mitochondrial membrane integrity (Brand and Nicholls, 2011;Cossins and Beevers, 1963;Logan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Dehydration of desiccation-sensitive tissues of pea and cucumber radicles was associated with the production of acetaldehyde, indicative of a switch to fermentation, possibly triggered by a disruption of flux through glycolysis, the tricarboxylic acid cycle, or oxidative phosphorylation (Leprince et al ., 2000). Volatile production during deterioration of recalcitrant seeds is not widely reported in the literature, although a study of four recalcitrant species ( Ligustrum japonicum , Quercus serrata , Quercus myrsinaefolia , and Camellia japonica ) found that seeds produced methanol, ethanol, and acetaldehyde during storage, and that the application of exogenous acetaldehyde accelerated deterioration (Akimoto et al ., 2004). …”
Section: Introductionmentioning
confidence: 99%
“…To test whether low molecular weight lipid peroxidation byproducts could influence seed fate, we presented red oak seeds coated with acetaldehyde to squirrels. Given that lipid peroxidation is potentially involved in the breakdown of waxes in red oak acorns, release of byproducts including acetaldehyde from seeds may be expected (Akimoto et al 2004). Our results show that acetaldehyde-treated seeds were 7 times more likely to be consumed than control seeds (Table 2).…”
Section: Discussionmentioning
confidence: 70%